Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Konsumen Nature Republic di Surabaya - Annisa Ristanti; Sri Setyo Iriani (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Korean wave's existence makes Indonesian people interested in Korean cosmetics. One of the most favored Korean cosmetic brands in Indonesia is the Nature Republic, they have problems regarding the counterfeiting and illegal smuggling of some of their products. The purpose of this research is to analyze and discuss the influence of product quality and brand image on Nature Republic consumer purchasing decisions in the city of Surabaya. This research is a conclusive study with quantitative data analysis. Using a non-probability sampling technique with judgmental sampling. The number of samples in this study amounted to 110 respondents. The technique of collecting data using questionnaires that are used a Likert scale as the measurement and using multiple linear regression analysis techniques with application computer program SPSS 25 for Windows. The results of multiple linear regression analysis showed that product quality has a significant influence on purchasing decisions with a significant value of 0.003. As well as the brand image variable which has a significant value of 0,000, so that the brand image variable is known to have a significant influence on purchasing decisions. The indicator with the highest value of product quality is the impression of quality, then the brand image is the product image. Based on the results and discussion of the research, the managerial implications that can be applied are maintaining and improving product quality and brand image to increase consumer demand, have a competitive advantage, and benefit the company in terms of market expansion.